The Impact of Digital Payment Systems on Small and Medium Enterprise (SME) Growth - Anita Fatmawati; Raihan Fikri Azis (International Forum of Researchers and Lecturers, 2024)
This study explores the influence of digital payment systems on the growth of small and medium enterprises (SMEs). Utilizing a quantitative approach, the research examines key indicators of SME growth, such as sales, customer base expansion, and transaction efficiency, before and after adopting digital payment systems. Findings reveal a significant positive correlation between digital payment adoption and SME growth metrics, suggesting that digital transformation in payments is instrumental in enhancing financial performance and market reach for SMEs.